Combatting mobile phone scams - Cheong, Damien D. (2024)
Online scammers have been manipulating victims to install malware on their mobile phones, which facilitate unauthorised access to bank and other accounts as well as data theft. Financial losses among Singapore mobile phone subscribers have been significant. Installation of antivirus software and the Scam Shield app on mobile phones is a crucial first step to mitigate such threats.